2018
DOI: 10.1002/bab.1660
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a human lysosomal recombinant iduronate‐2‐sulfatase produced inPichia pastoris

Abstract: Hunter syndrome (Mucopolysaccharidosis II, MPS II) is an X-linked lysosomal storage disease produced by the deficiency of the lysosomal enzyme iduronate-2-sulfatase (IDS). Currently, MPS II patients are mainly treated with enzyme replacement therapy (ERT) using recombinant enzymes produced in mammalian cells. As an alternative, several studies have shown the production of active and therapeutic forms of lysosomal proteins in microorganisms. In this paper, we report the production and characterization of a reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
4
14
0
3
Order By: Relevance
“…On the other hand, cellular uptake of the recombinant enzymes in fibroblasts was only observed with 50 nM (Figure 1c,d), while at a lower concentration (10 nM) no differences were observed compared to the control. These results of cellular uptake are in agreement with reports about other recombinant lysosomal enzymes produced in P. pastoris without any modification in the N-glycans structure, such as α-glucosidase (Chen et al, 2000), acid lipase (phLA) (Du et al, 2001;Du et al, 2005), GALNS (Rodriguez-Lopez et al, 2016;Rodriguez-Lopez et al, 2019) and IDS (Pimentel et al, 2018). The N-glycosylation pattern of recombinant acid lipase and GALNS produced in the same strain P. pastoris used in this study, showed that both capped-and uncapped-phosphorylated mannoses were present in the recombinant enzymes, which could suggest that presence of those uncapped-phosphorylated mannoses F I G U R E 1 Cellular uptake of recombinant enzymes.…”
Section: Cellular Uptakesupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, cellular uptake of the recombinant enzymes in fibroblasts was only observed with 50 nM (Figure 1c,d), while at a lower concentration (10 nM) no differences were observed compared to the control. These results of cellular uptake are in agreement with reports about other recombinant lysosomal enzymes produced in P. pastoris without any modification in the N-glycans structure, such as α-glucosidase (Chen et al, 2000), acid lipase (phLA) (Du et al, 2001;Du et al, 2005), GALNS (Rodriguez-Lopez et al, 2016;Rodriguez-Lopez et al, 2019) and IDS (Pimentel et al, 2018). The N-glycosylation pattern of recombinant acid lipase and GALNS produced in the same strain P. pastoris used in this study, showed that both capped-and uncapped-phosphorylated mannoses were present in the recombinant enzymes, which could suggest that presence of those uncapped-phosphorylated mannoses F I G U R E 1 Cellular uptake of recombinant enzymes.…”
Section: Cellular Uptakesupporting
confidence: 91%
“…Cellular uptake assay was carried out as previously described (Mosquera et al, 2012;Pimentel et al, 2018;Rodriguez-Lopez et al, 2016). Briefly, 24 hr before the experiment, 1 × 10 5 cells/well of wild-type human skin fibroblasts or HEK293 (ATCC CRL1573)…”
Section: Cellular Uptake Of Purified Recombinant Hexosaminidasesmentioning
confidence: 99%
“…Finally, with the aim of reducing the costs of ERT or producing proteins with a potentially improved stability and pharmacokinetic and pharmacodynamic properties, alternative hosts have been evaluated for the production of recombinant enzymes [137]. The yeast Pichia pastoris and the bacterium Escherichia coli K12 have been used for the expression of IDS [138][139][140][141][142]. Although active, these enzymes need to undergo preclinical evaluations before being proposed for ERT.…”
Section: Improvements Of Ert Traditional Protocolmentioning
confidence: 99%
“…Likewise, it is well documented that human IDS overexpressed in mammalian cells showed 72–76 kDa precursors, which are converted into a phosphorylated form of 90 kDa and finally processed to mature forms of 55 and 45 kDa [35,36]. Moreover, human IDS have been expressed in P. pastoris , with a molecular mass larger than the one reported for the enzyme produced in mammalian cells [16]. The change in the molecular mass identified in this work could be due to hypermannosylation events, which are commonly observed in proteins expressed in P. pastoris [37], and to the fact that IDS sequence contains eight putative N-linked glycosylation sites [38].…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of recombinant IDS in Pichia pastoris GS115. The production of human recombinant IDS (rhIDS) in the yeast P. pastoris GS115 was carried-out as previously described [16]. Briefly, human IDS cDNA (GenBank accession number NM_000202.6, kindly donated by Dr. Shunji Tomatsu) was inserted in the pPIC9 plasmid (Thermo Fisher Scientific, San Jose, CA, US) downstream of the α-factor secretion signal from S. cerevisiae to produce pPIC9-IDS.…”
Section: Methodsmentioning
confidence: 99%